2020
DOI: 10.3847/1538-4357/ab61fa
|View full text |Cite
|
Sign up to set email alerts
|

Space Velocity and Time Span of Jets in Planetary Nebulae

Abstract: Fast highly-collimated outflows including bipolar knots, jet-like features, and point-symmetric filaments or string of knots are common in planetary nebulae (PNe). These features, generally named as jets, are thought to play an active role in the nebular shaping immediately before or at the same time that fast stellar winds and D-type ionization fronts shock and sweep up the nebular envelope. The space velocity, radial distance from the central star and kinematic age of jets in PNe cannot be determined because… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 101 publications
2
16
1
Order By: Relevance
“…The expansion velocity of our toroidal structure of order 10-30 km s −1 (Fig. 5f) and the 90 − 130 km s −1 bipolar outflow are broadly consistent with observations of young (proto-)PNe and post-AGB stars (Imai et al 2002;Tafoya et al 2020;Guerrero et al 2020). This shows that our proposed mechanism self-consistently reproduces the structures observed in such systems.…”
Section: Comparison To Observationssupporting
confidence: 88%
See 1 more Smart Citation
“…The expansion velocity of our toroidal structure of order 10-30 km s −1 (Fig. 5f) and the 90 − 130 km s −1 bipolar outflow are broadly consistent with observations of young (proto-)PNe and post-AGB stars (Imai et al 2002;Tafoya et al 2020;Guerrero et al 2020). This shows that our proposed mechanism self-consistently reproduces the structures observed in such systems.…”
Section: Comparison To Observationssupporting
confidence: 88%
“…This suggests that at least a large fraction of PNe originates from common-envelope interaction in binary stellar systems, where a star spirals into the envelope of a giant and eventually ejects it (Paczynski 1976;Nordhaus & Blackman 2006;De Marco 2009;Boffin & Jones 2019). Bipolar PNe are often observed to consist of two main components (Sahai & Trauger 1998): a toroidal structure of slowly expanding gas (≈ 20 km s −1 ) and a perpendicular, fast bipolar (sometimes jet-like) outflow (≈ 70 km s −1 , in many cases exceeding 100 km s −1 , see Imai et al 2002;Tafoya et al 2020;Guerrero et al 2020). Magnetic fields have been inferred in such bipolar outflows, e.g., from synchrotron emission (Perez-Sanchez et al 2013), dust continuum polarization (Sabin et al 2015) and maser emission (Miranda et al 2001), and are thought to help collimate them (Vlemmings et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore more reasonable to suppose that the knots were directly ejected as dense bullets from the central star system, in which case the measured mass loss rate is a true reflection of the mass loss in the collimated outflow. Guerrero et al (2020) studied the kinematics of jets in a sample of 58 planetary nebulae. They found that the observed distribution of radial velocities can be reproduced by a bimodal distribution of threedimensional space velocities: 70% of nebulae have low-velocity jets with 𝑉 = (66 ± 26) km s −1 , while 30% have high-velocity jets with 𝑉 = (180 ± 60) km s −1 .…”
Section: Lobes and Knotsmentioning
confidence: 99%
“…Since the early evidence for and detection of jets in planetary nebulae (PNe) (Feibelman 1985;Gieseking et al 1985;Miranda & Solf 1990;López et al 1993), a number of studies have expanded upon the idea that jets in PNe and proto-planetary nebulae (PPNe) are common instead of something exotic, especially after observations made with the Hubble Space Telescope (Borkowski et al 1997;Sahai & Trauger 1998) and ground-based CO millimeter observations (Alcolea et al 2000;Bujarraval et al 2001), which more recently include the Atacama Large Millimeter Array (ALMA) (Sánchez-Contreras et al 2018;Tafoya et al 2020). The list of studies is large, and a recent compilation is given in Guerrero et al (2020).…”
Section: Introductionmentioning
confidence: 99%